Tillvänjning av labradorer att skritta och trava på löpband - Honkavaara, Sofia (2007)
The aim of this study was to determine a method to habituate treadmill-naive Labrador Retrievers to walk and trot on a treadmill. 17 Labradors was equipped with reflective markers glued to the skin. Their motions were captured with six 240 Hz infra-red cameras as they walked and trotted on a treadmill three times a day for two days. Also the heart-rate was recorded. We then used QTM and custom built software to analyze the measurements. Statistical analyses of the angles displacement of the elbow and stifle joint and of the heart-rate were performed. The outcome of the results of the elbow in the walk and the heart-rate in the walk showed that the dogs tended to habituate to walk on the treadmill. The results of the analyses of the elbow in the trot and the stifle showed no signs of habituation. The results indicate that there were other factors that might influence the motion-pattern of Labrador Retrievers walking and trotting on a treadmill than habituation alone.